Analisis Structure, Conduct and Performance (SCP) pada Pemasaran Daging Sapi di Kabupaten Kubu Raya - Linda Yulinda Asri (Jurnal Ekonomi Pertanian dan Agribisnis, 2023)
Structural problems of domestic cattle and beef marketing include: marketing infrastructure, market structure and price formation, and the existence of domestic marketing policies and regulations. The purpose of this study was to determine the description of beef marketing in Sungai Subdistrict, Kubu Raya Regency and to calculate the marketing efficiency of beef cattle using market structure, market conduct, and market performance (SCP) analysis approaches. The research was carried out in November-December 2021. Respondents were 60 farmers, and 32 sub-district traders, district traders, and retailers. The method used is a survey using a questionnaire. Descriptive analysis for marketing margins and analysis of market structure, market behavior and market appearance. The results showed that beef marketing in Sungai Raya Subdistrict consisted of 3 marketing channels, namely: 1) Breeders – Collector Traders, Sub-District Traders – Retailers – Consumers; 2) Breeders – District Collectors – Retailers – Consumers. ; 3) Jakarta Retailers-PT Agro Boga Utama Pontianak (Prov Distributor)-Regency/City Traders in West Kalimantan Province-Consumers. With a market structure approach, the beef market in Sungai Raya District tends to be less concentrated (low concentration). From market behavior, the payment system is good. Meanwhile, market performance shows that the distribution of margin, farmer's share, and profit ratio is evenly distributed in each marketing institution. From the SCP indicators above, it can be seen that beef marketing in Sungai Raya District is efficient.